2018
DOI: 10.1371/journal.pgen.1007312
|View full text |Cite
|
Sign up to set email alerts
|

The receptor protein tyrosine phosphatase CLR-1 is required for synaptic partner recognition

Abstract: During neural circuit formation, most axons are guided to complex environments, coming into contact with multiple potential synaptic partners. However, it is critical that they recognize specific neurons with which to form synapses. Here, we utilize the split GFP-based marker Neuroligin-1 GFP Reconstitution Across Synaptic Partners (NLG-1 GRASP) to visualize specific synapses in live animals, and a circuit-specific behavioral assay to probe circuit function. We demonstrate that the receptor protein tyrosine ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 50 publications
4
29
0
Order By: Relevance
“…We established that like NLG-1 GRASP, NLG-1 CLASP labels connections between correct synaptic partners, and has a spatial pattern similar to that predicted by electron micrograph reconstruction (11,12). As a validation, NLG-1 CLASP labeling is disrupted by loss of the clr-1 gene, which is required for synaptic partner recognition (13).…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…We established that like NLG-1 GRASP, NLG-1 CLASP labels connections between correct synaptic partners, and has a spatial pattern similar to that predicted by electron micrograph reconstruction (11,12). As a validation, NLG-1 CLASP labeling is disrupted by loss of the clr-1 gene, which is required for synaptic partner recognition (13).…”
Section: Introductionsupporting
confidence: 63%
“…To determine if these puncta were indeed synaptic, we introduced NLG-1 CLASP into clr-1/RPTP synaptogenesis mutants. In clr-1/RPTP mutants, PHB-AVA NLG-1 GRASP fluorescence intensity is dramatically reduced, and a PHB circuit-specific behavior is disrupted, indicating a reduction in synaptogenesis between the two neurons (13). We found that NLG-1 CLASP fluorescence intensity was also dramatically reduced in clr-1/RPTP mutants ( Fig.…”
Section: Nlg-1 Clasp Visualizes Specific Subsets Of Synapses In Live mentioning
confidence: 55%
See 2 more Smart Citations
“…FlincG3 allows visualization of cGMP production in PHB chemosensory neurons in response to the repellent SDS. (A) Diagram of the PHB circuit; this figure is reproduced from Figure 1C in Varshney et al (2018) under the Creative Commons Attribution License (https://creativecommons.org/licenses/by/4.0/). The primary postsynaptic partners of PHB neurons are the AVA backward command interneurons and the PVC forward command interneurons (Hilliard et al 2002; Park et al 2011; Tran et al 2017).…”
Section: Resultsmentioning
confidence: 99%